THE ROLE OF POLICE IN ENSURING ECONOMIC SECURITY AND THE POTENTIAL TO ENHANCE THIS ROLE - Altansukh Norov; Urjin Odkhuu (International Journal of Innovative Technologies in Social Science, 2025)
The police play a crucial role in ensuring Mongolia’s economic security and the stability of the financial sector, particularly in effectively combating serious economic crimes like money laundering. To assess the current state of police involvement in economic security and anti-money laundering efforts, the SWOT-AHP analysis method was utilized. This analysis aimed to evaluate the present situation, future economic security, and potential for increased police participation in combating money laundering. Internally, the police organization’s strengths include specialized teams, internal cooperation, and a structure to track illicit financial flows. However, weaknesses such as insufficient human resources, weak technology and innovation, and inadequate data supply for monitoring money flow were identified. Externally, favorable conditions like a strong legal framework, international financial support, and opportunities for knowledge exchange were noted. Conversely, challenges such as low public awareness, international crime networks, and political and economic influences were identified as potential obstacles. Overall, enhancing police capabilities and addressing weaknesses will be crucial in ensuring economic security and combating money laundering effectively.